FACTORS AFFECTING THE STOCK PRICES OF MANUFACTURING COMPANIES LISTED ON THE IDX BEFORE AND DURING THE COVID-19 PANDEMIC - Audrey, Audrey; Yanti, Yanti (Graduate Program of Universitas Tarumanagara, 2023)
The purpose of this study is to examine the factors that affect stock prices as well as to examine the differences in stock prices before and during the COVID-19 period. The research methods used are multiple linear regression analysis and different tests through the IBM SPSS 26 program. The sampling technique used is purposive sampling which resulted in 82 manufacturing companies listed on the IDX. The results of the regression test before COVID-19 period shows that EPS, PER, and WCTO have an effect on stock prices, while DER and IVTO have no effect on stock prices. The results of the regression test during the COVID-19 period showed that EPS has an effect on stock prices, while PER, DER, WCTO, and IVTO had no effect on stock prices. The result of the different test shows that there is no difference in the average stock prices before and during the COVID-19 period.